Association of mutations and polymorphic variants of the VHL gene with the clinical characteristics of retinal capillary hemangioma - V. V. Neroev; S. V. Saakyan; A. Yu. Novikova; M. V. Ryabina; P. A. Ilyukhin; A. Yu. Tsygankov; V. I. Loginov; A. M. Burdenny (Российский офтальмологический журнал)
Purpose. To study the association of mutations and polymorphic variants of the VHL gene with the clinical characteristics of retinal capillary hemangioma.Material and methods. 29 DNA samples isolated from peripheral blood leukocytes of patients with retinal capillary hemangiomas were tested. The analysis of mutations and polymorphic markers of the VHL gene was carried out by high resolution melting curve analysis.Results. A significant correlation was found between the frequency of tyrosine mutation in the 156th position of the VHL gene and the localization of the capillary hemangioma in the middle periphery of the fundus, the presence of local exudative retinal detachment and fibroglial proliferation in the tumor region (p = 0.02; RR = 1.86). An association was established between arginine mutation frequency in the 200th position of the gene with the presence of cerebellar hemangioblastoma and spinal cord. A statistically significant association of the GA genotype of the polymorphic marker rs779805 of the VHL gene with the localization of capillary hemangioma in the middle periphery of the fundus was established (p = 0.03; RR = 4.8). It has been shown that the carriage of the T allele of the polymorphic marker rs779808 may be associated with the characteristic localization of the tumor at the extreme periphery of the retina in the upper temporal quadrant. A tendency to increasing frequency of occurrence of the AC genotype of the polymorphic marker rs1678607 in patients with hemorrhagic complications of capillary hemangioma, as well as to increasing frequency of the TT genotype of the polymorphic marker rs1642742 in patients with cerebellar hemangioblastomas was determined.Conclusion. Further research involving more clinical material is needed, as our results may be important for early diagnosis of Hippel — Lindau disease, prediction of the onset and clinical course of retinal capillary hemangiomas, as well as of the probability of systemic manifestations of the disease.